ASAS-ASAS HUKUM MODERN DALAM HUKUM ISLAM - Muhammad Alim (Jurnal Media Hukum, 2010)
The legal principle is important because it is the truth which is used as a base of thinking and reasoning, especially in the law enforcement and implementation. The principle of law is the most important subsystem of one system of law and legal principle. The principle ranks above the rule system. It is not only because the principle of the law is more universal in character, but also because it reflects the values and cultural message which should be embodied in the rule of law. Theprinciple of law may be cited as the basis or reason for the formation of a rule of law or is a ratio legis of legal rule that contains the values, spirit, ideas of social or ethical views to be established. In the view of Islam, as mention in the Quran, Islam is a complete and perfect teachings. Completeness and perfection is spoken by Allah Almighty in the Quran sura Al Maaidah/5: 3. Although the rule of Allah in the teaching of Islam is perfect, the principle of Islamic law which is still considered legal principles derived from western scientific thought.Keywords: Modern Islamic Principles of Law, The legal principle, the law enforcement.